The Effect of The Density of Cucumber Nested with The Potato Crop to Reduce The Damage of The White Fly And Its Effect on 2 - The Population Density of The Insect and Some Characteristics of The Quantitative Yield of The Potato Crop - Al- Shammari, Aziz M. A.; Al Bayati, Kareem A.H.; Sameen, Asmaa Yahya (Journal of agricultural, environmental and veterinary sciences, 2019)
The experiment was conducted in the agricultural fields in the province of Kirkuk in the autumn season 2017 to study the effect of the density of cucumber plant nested with the potato crop on the population density of the white fly and some qualities of the quantity of potato. The study included two factors the first three varieties of potatoes Actrice, Alaska and Oxyania, The second factors is four levels of The density of cucumber plant grown with the potato crop (0, 1, 2 and 3 cucumber plants) for each experimental unit, (which is 3 m2). The experiment contained twelve treatments resulting from the compatibility of the above factors with three replicates; the differences between the averages were tested according to the Duncan multidimensional test at a probability level 0.05. The results showed: The plants of the Actrice variety contained the lowest number of white fly insects on the leaves (12.90 insects per ten leaves). The cucumber cultivar was nested with the potato and the density of two plants per experimental unit (3 m2) resulted in the lowest number of insects with 6.03 insects per ten leaves of the potato crop. The results showed that the superiority of the Actrice variety significantly improved the total yield of the plant (815.00 gm-1) and the marketable yield of one plant (676.9 gm-1) and the total marketable yield (36.10 tons h-1)), while Oxyania was higher in the average weight of the tuber for the marketable crop (93.85 g). The results showed that the cucumber varieties was nested with potato plant and the density of two plants of the experimental unit give the best values in the total number of tubers (11.838 (tuber-1) and the number of tubers marketed (9.946 tuber-1) and the marketable yield of the plant (724.1 gm) The total yield of the plant was (852.778 gm) and the total marketable yield (38.62 tons.)